Pengaruh Self Confidence Terhadap Kemamapuan Berpikir Kritis Matematis - Danil Saputra; Tasnim Rahmat; M. Imamuddin; Ulva Rahmi (International Forum of Researchers and Lecturers, 2024)
This study aims to determine the significant effect of self confidence on students' critical thinking skills. The hypothesis in this study is that there is a significant effect of self-confidence on the ability to think critically mathematically.This type of research is correlational. The population in this study were all VIII grade students as many as 6 classes totaling 188 students. The research sample was taken randomly 30 students. The data in this study are in the form of self confidence questionnaire and mathematical critical thinking skills questions. The data analysis technique uses correlation analysis. The results of this study obtained t_0 = 3.391 and t_table = 1.70 at the real level α = 0.05. This shows that t_0> t_table which means H_(0) is rejected or H_1 is accepted which states that there is a significant effect of self confidence on the critical thinking skills of class VIII students. The effect of self-confidence on mathematical critical thinking ability is a moderate relationship with r_(Xy) = 0.54 and obtained a coefficient of determination of 29.16%